PENGARUH PROFITABILITAS, LIKUIDITAS, DAN CAPITAL INTENSITY TERHADAP AGRESIVITAS PAJAK - Devanty, Pipit Ritma; Widiawati, Hestin Sri; Faisol, Faisol (Universitas Nusantara PGRI Kediri, 2023)
This study aims to know the influence of profitability, liquidity, and capital intensity on tax aggressiveness in mining sector companies listed on the Indonesia Stock Exchange during the 2020-2022 period. The method used in this research is quantitative causality and the sampling method uses purposive sampling. The sample in this study consisted of 14 companies listed on the Indonesia Stock Exchange during the 2020-2022 period. The analysis technique used in this research is panel data regression using Stata software version 14. The results of this study indicate that profitability, liquidity, and capital intensity have no effect on tax aggressiveness. The difference between this research and previous studies is the time and data studied.